Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

If f(x) + x^2 * f(x) = 10 and f(1)=2, find f'(1).

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Join Brainly to access

this expert answer

SIGN UP FOR FREE
check ur ques. again its wrong it does not satisfy for f(1)=2 in the main equation
well that's the friggen problem verbatim from the textbook
OH pellet

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

it's not sorry geez sorry it's f(x) + x^2 * f(x)^3 = 10 the second f(x) term is cubed
Maybe rearrange the problem a bit....\[y+x^2y=10\implies y=\frac{10}{1+x^2}\]I don't think your problem meets the specified conditions.
is ur anwer 2/5??
it's -16/13 that's the answer in the book
animalain - it's y + (x^2)(y^3) = 10
Yeah, I got that. Trying to figure out my strategy....
yeah its done
...
How did you do it?
differentiate it n then put x=1 in equation u'll get the result
is that done??
\[y + (x^2)(y^3) = 10\implies y'+2xy^3+3x^2y^2y'=0\]\[\implies y'(1+3x^2y^2)=-2xy^3\implies y'=\frac{-2xy^3}{1+3x^2y^2}\]\[\implies y'(1)=\frac{-16}{13}\]Got it. Need to practice my calculus a little more....LOL
all the best..:)

Not the answer you are looking for?

Search for more explanations.

Ask your own question